Public Spending on Health Care and the Poor - Verhoeven, Marijn (IMF Working Papers; Working Paper ;, 2001)
This paper estimates the impact of public spending on the poor's health status in over 70 countries. It provides evidence that the poor have significantly worse health status than the rich and that they are more favorably affected by public spending on health care. An important new result is that the relationship between public spending and the health status of the poor is stronger in low-income countries than in higher-income countries. However, the results suggest that increased public spending alone will not be sufficient to meet international commitments for improvements in health status.